PHARMACEUTICAL CARE OF ACNE PATIENTS USING SYSTEMIC RETINOIDS - Yuliya Nastyukha; Andriy Zimenkovsky; Diana Klapko (Acta Medica Leopoliensia)
Aim. The research aims to study of the issue of pharmaceutical care of acne patients when using systemic retinoids.